Origin of Ti-Fe-oxide mineralization of post-island-arc gabbroid complexes in the northern part of the West Magnitogorsk zone (Southern Urals) - I. R. Rakhimov; A. V. Vishnevskiy (Georesursy, 2024)
Detailed mineralogical and geochemical studies of Ti-Fe oxides from gabbroids of the Nauruz and Utlyktash post-subductional complexes, West Magnitogorsk Zone, South Urals, have been carried out. The polygenic nature of Ti-Fe mineralization in Nauruz sill, Utlyktash layered lopolith and Uraz intrusion rocks has been established. The Nauruz massif is dominated by titanomagnetite, which crystallized both from the Ti-Fe-oxide liquid at the early magmatic stage and from the residual Ti-Fe-enriched silicate melt at the intermediate and late magmatic stages (~970–800°C). The most rich in Ti-Fe oxides (Fe2 O3 * up to 20.1 wt %, TiO2 up to 1.6 wt %, and V up to 430 ppm) is the middle zone of the sill associated with intrusion of magma enriched in orthopyroxene phenocrysts. Both titanomagnetite and ilmenite are widespread in the Utlyktash lopolith, forming the richest accumulations in the lower part of the massif (Fe2 O3 * up to 18.1 wt %, TiO2 up to 2.9 wt %, and V up to 545 g/t) due to gravitational settling of crystallizing phases. The gabbroids of the Uraz intrusion are similar in mineral and chemical composition, but differ from the Utlyktash lopolith in the patterns of formation of Ti-Fe mineralization, which requires a special study. In general, the geological settings for the formation of the Nauruz sill and Utlyktash lopolith are quite favorable for the formation of economic Fe-Ti ores.